DESAIN PRIMER PCR SECARA IN SILICO UNTUK AMPLIFIKASI GEN COI PADA KUPU-KUPU Papilio ulysses Linnaeus DARI PULAU BACAN - Suparman, Suparman (Jurnal Pendidikan Matematika dan IPA, 2016)
The insillico research was conducted to produce primer sequence of COI gene in Butterfly species Papilio ulyses from Bacan Island that will be used in gene isolation. The COI sub-unit I is a barcode gene that generally have special purposes in animal identification. It is also available in phyilogenetic analysis. The first step of method is downloading the COI DNA sequence of Papilio ulysses from GeneBank (NCBI). Then the conserve region of COI sequence is identified to determine primer. Primer is designed with primer designer software (Genamics Expression) in two direction of DNA reading frame that are : forward primer (COI Pu-F) and reverse primer (COI Pu-R). The last step is primer confirmation with primer blast tool in NCBI. Primers of COI gene that are produced consist of two, that are CGAAAATGACTTTATTCAACA for forward primer (COI Pu-R) and AGCAGTAATTCCAACAGCTC for reverse primer (COI Pu-R). The optimal temperature of annealing is from 50,740 to 55,740 Celsius with PCR product around 567 base pair long. Key Words : PCR primer, in silico, COI gene, Papilio ulysses, Bacan island.